Pengaruh Konten Instagram @mynewlyfe.id dan Personal Selling terhadap Keputusan Menjadi Nasabah - Sharon Astrid Valentina Imanuella Linanto; Widya Natassha Rachim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Marketing strategy is a series of activities carried out by company to achieve specific marketing objectives. Instagram content is one of the marketing strategies used by Manulife to deliver information to audiences with the aim of influencing them to become customers. In the digital era, where many companies maximize the use of social media, Manulife still used personal selling. Through personal selling, consumers can ask questions and receive information directly, in a detailed and structured manner, while also building closer relationships between sellers and customers. This study aims to determine the influence of Instagram content and personal selling on customer decision-making, using a quantitative approach with 96 respondents, determined using the Rao Purba formula. The results show that Instagram content from @mynewlyfe.id has a significant influence on customer decisions by 38.8%, with a t-value of 3.917 and a significance level of <0.05. Personal selling also significantly affects customer decisions by 36.2%, with a t-value of 3.848 and a significance level of <0.05. Simultaneously, both variables contribute 36.7% to customer decision-making. These findings indicate that Instagram content from @mynewlyfe.id has a moderate influence on customer decisions; personal selling also has a moderate influence; and both, Instagram content and personal selling simultaneously affect customer decisions by 36.7%.